ANALISIS PEMASARAN AGROINDUSTRI KUE BOLU DI KECAMATAN KUOK KABUPATEN KAMPAR - Dian Wulandari; Evy Maharani; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research goal is to identify marketing channels, marketing margin and marketing efficiency. This research was conducted in the village of Kuok Kuok District of Kampar regency. The method used in the study using survey methods, sampling purposive sampling. The sample consisted of a sponge cake agroindustry entrepreneurs and 30 customers sponge cake. The data used in this study are primary data and secondary data. Agroindustry research results sponge cake has a marketing channel of entrepreneurs to consumer marketing channel efficiency Rated sponge cake made at home by 8.06% more efficient than the efficiency of marketing channels is done in the market Bangkinang by 15.56%, due to marketing channels in Bangkinang market while the cost of transportation for marketing in the home does not use transport. Value marketing channel efficiency sponge cake made in the market Air Tiris by 13.23% more efficiency than do marketing channels in the market Bangkinang by 15.56%, due to marketing in Bangkinang done every 5 days a week so that the transport is greater than transport to Air Tiris that marketing is done every once a week. The value of marketing efficiency in marketing channels carried in Rumbio market is 13.66% larger than marketing channels Air Tiris performed in the market, namely 13.23%, because many employers bring cakes to Air Tiris market.   Keyword: Marketing, Channel, Cost, Margin, Efficiency